1960
DOI: 10.1029/jz065i002p00609
|View full text |Cite
|
Sign up to set email alerts
|

Short-wave fadeouts without reported flares

Abstract: Short‐wave fadeouts were sought which had no associated Hα flare. To carry out this study, Sacramento Peak flare patrol films were re‐examined for those days on which short‐wave fadeouts (SWF's) had occurred during patrol times without reported flares. Fifteen such fadeouts were reported during the IGY period. Upon re‐examination of the films, 12 of the SWF's were found to be in close time association with outstanding Hα events, usually in the nature of pronounced plage brightenings. In 2 other cases, seeing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Solar extreme ultraviolet (EUV) and X-rays propagate at the speed of light and take only ≈8 min to reach Earth's atmosphere, so SWF is one of the earliest space weather effects following a flare. This geophysical phenomenon was first described by J. H. Dellinger in 1935(Dellinger, 1937) and a later statistical study (DeMastus & Wood, 1960) showed that there is a one-to-one relation between solar flares and SWF. A recent study by Zawdie et al (2017) showed that plasma density enhancement is the main driver of HF radio wave absorption in D and E layers.…”
Section: Introductionmentioning
confidence: 83%
“…Solar extreme ultraviolet (EUV) and X-rays propagate at the speed of light and take only ≈8 min to reach Earth's atmosphere, so SWF is one of the earliest space weather effects following a flare. This geophysical phenomenon was first described by J. H. Dellinger in 1935(Dellinger, 1937) and a later statistical study (DeMastus & Wood, 1960) showed that there is a one-to-one relation between solar flares and SWF. A recent study by Zawdie et al (2017) showed that plasma density enhancement is the main driver of HF radio wave absorption in D and E layers.…”
Section: Introductionmentioning
confidence: 83%
“…SWF was discovered for the first time in 1935 (Dellinger 1937). The early statistical studies show a one-to-one correlation between SWF and solar flares, with the occurrence of SWF increasing as solar activity increases (DeMastus & Wood 1960;Hendl & Skrivanek 1973). Additionally, SWF generally occurs about 1-3 minutes after the flare erupts due to the ionospheric sluggishness (Appleton 1953;Chakraborty et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This sudden enhancement of electron density leads to an increase in ionospheric high-frequency (HF: 3-30 MHz) radio wave absorption that disrupts over-the-horizon (OTH) communication, commonly known as the Dellinger effect or shortwave fadeout (SWF) (Dellinger, 1937). A statistical study by DeMastus and Wood (1960) showed there is almost a one-to-one relationship between an earthward directed solar flare and the occurrence of SWF. More recent studies have shown how the duration and intensity of SWF depend on duration and peak intensity of the solar flare, location of the transmitter and receiver, frequency of the radio wave, and the background ionosphere (Chakraborty et al, 2018;Fiori et al, 2018).…”
mentioning
confidence: 99%